Compost enriched with ZnO and Zn-solubilising bacteria improves yield and Zn-fortification in flooded rice - Zeb, Hassan; Hussain, Azhar; Naveed, Muhammad; Ditta, Allah; Ahmad, Shakeel; Jamshaid, Muhammad Usman; Ahmad, Hafiz Tanvir; Hussain, Muhammad Baqir; Aziz, Riffat; Haider, Muhammad Sajjad (Italian Journal of Agronomy, 2018)
Zinc (Zn) is an essential element for humans, animals and plants, however, its deficiency has been widely reported around the world especially in flooded rice. Adequate amount of Zn is considered essential for optimum growth and development of rice. We hypothesised that management practices like Zn-mineral fertiliser, -compost, and -solubilising bacteria would improve Zn availability and uptake in flooded rice. A series of studies were conducted to find out the comparative efficacy of Zn-enriched composts (Zn-ECs) with Zn solubilising bacteria (ZnSB) vs. ZnSO4 for improved growth, yield and Zn accumulation in rice. There were six treatments viz. control, ZnSB, ZnO (80% Zn), ZnSO4 (33% Zn), Zn-EC80:20 and Zn-EC60:40. In all the treatments, Zn was applied at the rate of 5 kg ha–1 except the control. The treatment Zn-EC60:40 resulted in the maximum Zn release in soil as compared to ZnSO4 and all other treatments during incubation study. The treatment Zn-EC60:40 significantly improved root dry weight, grain yield and 100-grain weight of rice by 15, 22 and 28%, respectively as compared to ZnSO4. The same treatment resulted in the maximum increase in photosynthetic rate (11%), transpiration rate (21%), stomatal conductance (17%), chlorophyll contents (8%) and carbonic anhydrase activity (10%) while a decrease of 27% in electrolyte leakage was observed in comparison with ZnSO4 application. Moreover, the maximum increase in grain quality parameters and Zn bioaccumulation was observed with the application of Zn-EC60:40 in comparison with ZnSO4 application and all other treatments. We conclude that Zn-EC60:40 are not only an effective strategy to improve growth, physiology and yield parameters of rice, but also to improve the grain quality and Zn-bioaccumulation in rice compared to ZnSO4.